Psychosexual Consequences of Female Genital Mutilation and the Impact of Reconstructive Surgery: A Narrative Review - Laura Chiappa; Giussy Barbara; Massimiliano Brambilla; Paolo Vercellini (Mary Ann Liebert, 2019)
Purpose: We aim to provide a comprehensive overview of the health consequences of female genital mutilation/cutting (FGM/C), with a particular focus on the psychosexual implications of this practice and the overall impact of reconstructive plastic surgery. Methods: A MEDLINE search through PubMed was performed to identify the best quality evidence published studies in English language on long-term health consequences of FGM/C. Results: Women with FGM/C are more likely to develop psychological disorders, such as post-traumatic stress disorder, anxiety, somatization, phobia, and low self-esteem, than those without FGM/C. Most studies showed impaired sexual function in women with FGM/C. In particular, women with FGM/C may be physiologically less capable of becoming sexually stimulated than uncut women. Reconstructive surgery could be beneficial, in terms of both enhanced sexual function and body image. However, prospective studies on the impact of reconstructive surgery are limited, and safety issues should be addressed. Conclusion: Although it is clear that FGM/C can cause devastating immediate and long-term health consequences for girls and women, high-quality data on these issues are limited. Psychosexual complications need to be further analyzed to provide evidence-based guidelines and to improve the health care of women and girls with FGM/C. The best treatment approach involves a multidisciplinary team to deal with the multifaceted FGM/C repercussions.